Celebrity Endorser, Citra Merek dan Harga Sebagai Penentu Keputusan Pembelian - Muhammad Abbas (Economics and Digital Business Review, 2022)
Skincare is one of the primary needs that is currently a trend among the community, especially in Makassar City. As more and more beauty clinics in Indonesia offer similar products and treatments, the competition between these beauty brands increases, so Ms Glow must create something good in the eyes of the public. This research needs to be done to analyze and find out how the influence of the use of celebrity endorsers, brand image and price on purchasing decisions of Ms Glow products. This type of research is a type of quantitative descriptive research. The population in this study is the consumer product of Ms.Glow's basic facial package in Makassar City. The sampling method uses a non-probabilty technique, namely accidental sampling. The number of respondents in this study were 50 people (women). Methods of data collection using a questionnaire. The data analysis technique is using Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely the coefficient of determination test, F test and t test. The results of the study found that celebrity endorser, brand image and price had a positive and significant effect on purchasing decisions for Ms.Glow products in the people of Makassar City, either partially or simultaneously.